Wheel–Ground Interaction Test for Sugarcane Cargo Transshipments - Marques Filho, Aldir Carpes; Martins, Murilo Battistuzzi; de Medeiros, Simone Daniela Sartório; Santana, Lucas Santos; Lopes, Arthur Gabriel Caldas; Lanças, Kléber Pereira [UNESP] (Springer Nature, 2024)
Sugarcane cultivation involves several operations with vehicle traffic. Tires for cargo vehicles are responsible for soil compaction, which is the main impact caused by machines in agriculture. Thus, the present research aimed to evaluate load wheelsets interaction on deformable and rigid running surfaces. We use three tire models used on transshipment vehicles to sugarcane crops, one road and two agricultures, described as p1, double road radial wheelset; p2, agricultural radial tire; and p3, bias ply tire. We adopted a completely randomized design with three replications, for the total contact area and punctual area claws. In the deformable surface, the resistance to soil penetration was verified. Road tires had the largest punctual contact area to the total area, the total area/punctual area ratio was 66.9% in double road radial tire (p1), 34.8% in agricultural radial tire (p2) and 54.8% in bias ply tire (p3). Road tires may be applicable in situations where traffic is controlled in the field; however, for areas where traffic control measures are not applied, the radial tire has better performance. In a deformable surface, the contact areas increase in relation to the rigid surface, this occurs due to the soil particles rearrangement, and this causes the compaction process. Higher soil penetration resistance was obtained by bias ply and road tires (p1 and p3), and their application must be careful in sugarcane crops, mainly under conditions of high soil moisture.
Keywords: Cone index; Footprint; Mechanization; Soil compaction; Tire test